The reinstatement of Latace Phil. (Amaryllidaceae, Allioideae) - Sassone, Agostina Belen; Belgrano, Manuel J.; Guaglianone, Encarnación Rosa (Phytotaxa, 2015)
The monotypic genus Latace has been formerly treated under its related genera Leucocoryne or Nothoscordum. The genus Zoellnerallium, on the other hand, was established to include the atypical Nothoscordum andinum (= Ornithogalum andinum) and, later another similar species, namely Nothoscordum serenense, was also placed in this genus. In this contribution we corroborate that Latace and Zoellnerallium are names applied to the same taxon, and different from Nothoscordum and Leucocoryne. According to the priority rule, Latace is the name to be used instead of Zoellnerallium. Consequently, the name Latace is reinstated, while Zoellnerallium is relegated to the synonymy, and three new combinations are proposed: Latace andina f. andina, Latace andina f. lutea and Latace serenense. In addition, the chromosome identity of Latace (= Zoellnerallium) and morphological features that support Latace as an independent unit are herein highlighted, and presented together with keys to related genera and to species of Latace; lectotypes, neotypes, a distribution map, and illustrations are also included.